Role of transcription factors in porcine reproductive and respiratory syndrome virus infection: A review - You, Xiangbin; Lei, Ying; Zhang, Ping; Xu, Dequan; Ahmed, Zulfiqar; Yang, Youbing (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is an infectious disease caused by the PRRS virus that leads to reproductive disorders and severe dyspnoea in pigs, which has serious economic impacts. One of the reasons PRRSV cannot be effectively controlled is that it has developed countermeasures against the host immune response, allowing it to survive and replicate for long periods. Transcription Factors acts as a bridge in the interactions between the host and PRRSV. PRRSV can create an environment conducive to PRRSV replication through transcription factors acting on miRNAs, inflammatory factors, and immune cells. Conversely, some transcription factors also inhibit PRRSV proliferation in the host. In this review, we systematically described how PRRSV uses host transcription factors such as SP1, CEBPB, STATs, and AP-1 to escape the host immune system. Determining the role of transcription factors in immune evasion and understanding the pathogenesis of PRRSV will help to develop new treatments for PRRSV.